Effect of supplementing diets with effective microorganisms on intake, growth and carcass characteristics of ross 308 broiler chickens - Mafiri, Matseko Nkele (University of Limpopo, 2014)
Two experiments were conducted to determine the effects of supplementing diets with effective microorganisms on intake, growth and carcass characteristics of Ross 308 broiler chickens. The first experiment determined the effect of supplementing diets with effective microorganisms on performance of unsexed Ross 308 broiler chickens aged one to three weeks. Two hundred unsexed day-old chicks were randomly assigned to five treatments with four replications, each replication having ten birds. A complete randomized design was used. The chickens were fed a grower diet supplemented with 0 (EM0), 30 (EM30), 50 (EM50), 70 (EM70) or 100 (EM100) ml of effective microorganisms per litre of water. Effective microorganism supplementation did not improve (P>0.05) diet and metabolisable energy intakes of the chickens. Effective microorganism supplementation reduced (P<0.05) growth rate and live weight of the chickens. Poorer (P<0.05) feed conversion ratios were observed in chickens supplemented with effective microorganisms. However, effective microorganism supplementation improved (P<0.05) crude protein retention of the chickens. Supplementation with effective microorganisms reduced (P<0.05) mortality rate of the chickens from 10 to 0 %. The second experiment determined the effect of supplementing diets with effective microorganisms on performance of male Ross 308 broiler chickens aged 22 to 42 days. The chickens were randomly allocated to five treatments with four replications, each replication having 10 birds. The chickens aged 21 days, weighing 474 ± 2g, were allocated to the treatments in a complete randomized design. The chickens were fed a grower diet supplemented with 0 (EMM0), 30 (EMM30), 50 (EMM50, 70 (EMM70) or 100 (EMM100) ml of effective microorganisms per litre of water. Effective microorganism supplementation did not improve (P>0.05) intake, DM digestibility, metabolisable energy, feed conversion ratio, fat pad weight and meat sensory attributes of the chickens. Effective microorganism supplementation reduced (P<0.05) growth rate, live weight and carcass weight of the chickens. However, effective microorganism supplementation improved (P<0.05) crude protein retention and crude protein content of meat of the chickens. Supplementation with effective microorganisms reduced (P<0.05) mortality of the chickens from 5 to 0 %. v It is concluded that effective microorganism supplementation to the diets of Ross 308 broiler chickens reduced growth rate and live weight of the chickens. However, effective microorganism supplementation improved crude protein retention and crude protein content of the meat of broiler chickens. Supplementation with effective microorganisms reduced mortality of the chickens to zero.
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2014
Keywords: Ross 308 broiler chickens; Supplementary diets of chickens; Chicken feeding; Chickens -- Breeding; Broilers (Chickens) -- Productivity; Poultry -- Feeding and feeds